Recognition by association: Within- and cross-modality associative priming with faces and voices. - Stevenage, Sarah V.; Hale, Sarah; Morgan, Yasmin; Neil, Greg J. (British Journal of Psychology, 2014)
Recent literature has raised the suggestion that voice recognition runs in parallel to face recognition. As a result, a prediction can be made that voices should prime faces and faces should prime voices. A traditional associative priming paradigm was used in two studies to explore within-modality priming and cross-modality priming. In the within-modality condition where both prime and target were faces, analysis indicated the expected associative priming effect: The familiarity decision to the second target celebrity was made more quickly if preceded by a semantically related prime celebrity, than if preceded by an unrelated prime celebrity. In the cross-modality condition, where a voice prime preceded a face target, analysis indicated no associative priming when a 3-s stimulus onset asynchrony ( SOA) was used. However, when a relatively longer SOA was used, providing time for robust recognition of the prime, significant cross-modality priming emerged. These data are explored within the context of a unified account of face and voice recognition, which recognizes weaker voice processing than face processing.